ALUR PENGELOLAAN DOKUMEN LAPORAN KAS HARIAN CV JADI BERKAT DAN OPTIMALISASI REKAP BIAYA MEMO ASET PADA DIVISI MANAGEMEN ASET CV BANYAK BERKAT - Tias, Putri Adining; Anggraini, Niken Ayu; Wahyuningsih, Dwi Warni (Jurnal Pijar, 2025)
Proper and well-documented daily cash management is essential for internal control, fund protection, and operational transparency. Standardized asset memo recaps help accurately track costs and asset depreciation, which affect financial reporting and company investment policies. This study uses a descriptive approach with field studies involving observation, interviews, and documentation studies. The results show that the implementation of procedures that include segregation of duties, multi-level authorization, and the use of a simple Accounting Information System (AIS) and standardized SOPs can improve the effectiveness of internal controls, reduce the risk of recording errors, and speed up the report reconciliation process. Key recommendations include developing document flowcharts, implementing daily cash and asset memo SOPs, using AIS for recapitulation automation, conducting periodic internal and physical asset audits, and providing regular training for officers. With integrated and standardized procedures, CV Jadi Berkat can significantly improve the accuracy of its financial reporting and the efficiency of its asset management.